2017
DOI: 10.4172/pharmaceutical-sciences.1000234
|View full text |Cite
|
Sign up to set email alerts
|

Hatice Asli Bedel, Nur Tukel Turgut, Aysegul Ugur Kurtoglu, Coskun Usta

Abstract: Bedel, et al.: Pharmacology of Punicic AcidPlant extracts and nutraceuticals are the most ancient and widespread form of medication employed by the general population. The pomegranate is a prehistoric, mystical and a highly differentiated fruit. Moreover, pomegranate is found in some medicinal systems as a cure for a variety of illnesses. Pomegranate has been used for a long time for nutraceutical purposes. Current research indicates that the most medicinally useful pomegranate components include ellagitannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…It has anti-inflammatory, antidiabetic, anti-carcinogenic properties due to which it has vital health implications (71).Studies have suggested that punicic acid may help to reduce inflammation in the body, which can help to protect against chronic diseases such as heart disease, diabetes, and cancer. It may also help to reduce oxidative stress, which is a key factor in aging and the development of chronic diseases (72). Figure 7 shows the biosynthestic pathway for the formation of punicic acid (71).…”
Section: Pomegranatementioning
confidence: 99%
“…It has anti-inflammatory, antidiabetic, anti-carcinogenic properties due to which it has vital health implications (71).Studies have suggested that punicic acid may help to reduce inflammation in the body, which can help to protect against chronic diseases such as heart disease, diabetes, and cancer. It may also help to reduce oxidative stress, which is a key factor in aging and the development of chronic diseases (72). Figure 7 shows the biosynthestic pathway for the formation of punicic acid (71).…”
Section: Pomegranatementioning
confidence: 99%